Cytodiagnosis of Primary Ewing Sarcoma of the Skull: Diagnostic Clues and Difficulties - Sukumaran, Renu; Nayak, Nileena (Annals of Pathology and Laboratory Medicine, 2021)
Ewing sarcoma is a rare primary neoplasm of bone representing approximately 6-8% of all malignant bone tumours. Because of its aggressive clinical behaviour and rapid dissemination to other sites, an early accurate diagnosis is of utmost importance. It shares morphological features with other round cell tumors. Common differentials include lymphoblastic lymphoma, neuroblastoma, rhabdomyosarcoma and neuroendocrine tumours. Due to the morphological overlap, critical evaluation of the cellular details is essential. Fine needle aspiration cytology becomes a successful diagnostic tool when the subtle diagnostic clues and difficulties are considered during diagnosis. Judicious use of ancillary techniques will also aid in arriving at an accurate diagnosis. We present the case of a seven-year-old boy who presented with painful swelling of the scalp. Aspiration smears were cellular and showed atypical small round cells. Evaluation of morphological details along with special stains and immunohistochemistry in cell block preparation aided in rendering a diagnosis of Ewing sarcoma. The awareness of overlapping features in clinical presentation, morphology and immunohistochemical findings will help to arrive in the proper diagnosis. Early diagnosis on cytology samples can help in timely initiation of treatment, thus improve prognosis.